Documenting torture and ill-treatment of children and adolescents: Current practices and challenges - Mukamel, Maya; Cohen, Keren (Torture Journal, 2019)
If we are to work effectively towards achieving the WHO 2030 target to end torture and ill-treatment of children or to support litigation, advocacy, representation and care for children and young people who have survived such experiences, we must have the right tools to do so. Children and young people are fundamentally different from adults and the guidelines require a different framework to reflect this.